Oral English Communication Expectations of Business Graduates in the Workplace in Sri Lanka - Wijewardene, Lishanthi (Advances in Social Sciences Research Journal, 2021)
Graduate employability is a topic of much discussion, and employability skills among graduates is an equally important topic of discussion, as it has been stressed in many scholarly articles that, most graduates do not possess employability skills. Among these skills, oral English proficiency rates high, as they play an important role in the employability and marketability of graduates. Much importance has been placed on English proficiency and good communication skills among graduates which will help in increasing their employability (Ting, Marzuki, Chuah, Misieng & Jerome, 2017). The results of a survey conducted amongst ten employers revealed that in order to be ‘employable,’, business graduates need to develop their oral English competencies, and that good English communication skills can increase the employability of graduates as English is particularly important for graduates (Shivakumar & Sharma, 2017). Thus this article intends to examine the oral English competency that graduates are required to possess, in order that they may be gainfully employed.